EIGHT KEYS BEFORE LEARNING TO SPEAK ENGLISH: (A Proposal for Motivating EFL Speaking Learners in Indonesia) - Abd Wafi (OKARA: Jurnal Bahasa dan Sastra, 2015)
Being able to speak English fluently is as measuring rod for someone who is said to be good at English. In Indonesian context, English is still as foreign language and this becomes problem for them who want to learn it. The problem could be caused by the difficulty of the English itself, the learners’ personality and the process in learning it. There are ample solutions to deal with those difficulties; however, the writer provides a solution as a proposal for motivating the learners; there are 8 keys to be possessed by the learners before they learn to speak English. They are (1) Listen up, (2) be good at imitating, (3) use the mouth, (4) check the voice, (5) have the motion, (6) smile, (7) thank God, and (8) love. The solution is as inner drive or  instrinsic motivation for the learners and it can also be used by the teachers, tutors and lecturers as reference for motivatingthe learners in learning or in mastering English speaking.